PERANCANGAN SIMULASI MITIGASI BENCANA GEMPA BERBASIS ROBLOX - Soeltan Abdul Ghaffar; Rilliandi Arindra Putawa; Calvina Izumi; Dwi Sugianto (Jurnal Manajemen Bencana (JMB), 2023)
One important application of metamesta is in natural disaster simulations, providing immediate benefits in disaster preparedness. These simulations are not only useful for volunteers but also for students. However, the implementation of disaster simulations in formal education remains ineffective in Indonesia. This research aims to design a comprehensive earthquake disaster simulation using metamesta technology, utilizing the Roblox platform. The design process involves interviewing potential users to determine their needs, creating prototypes, and establishing the simulation environment. Complex objects are crafted using Blender and imported into Roblox Studio. LUA programming code controls metaverse, while a GUI is used for the main menu. Testing is conducted to ensure proper functionality. Overall, the Roblox metaverse platform proves to be effective for disaster simulations, and future developments may integrate metaverse with the real world through the Internet of Things (IoT) for a more immersive early warning system.